A new species of the genus Solieria Robineau-Desvoidy (Diptera: Tachinidae) from Iran - Ebrahim Gilasian; Joachim Ziegler (Journal of Insect Biodiversity and Systematics)
The discovery of the Holarctic tachinid genus Solieria Robineau-Desvoidy, 1849, in Iran led to the identification of a new species to science, which is described here as Solieria variabilis sp. nov. It can be separated from other related species by the absence of discal setae on abdominal tergites, lack of proclinate and latero-reclinate orbital setae in the male, the width of frons, and by colouration and microtrichosity of abdomen. The comparison of the morphological characters of S. variabilis sp. nov. with its close relatives S. fenestrata (Meigen, 1824) and S. pacifica (Meigen, 1824) is provided. Photographic images of the habitus and head as well as illustrations of terminalia are given.